Effect of experimental orthodontic pain on gray and white matter functional connectivity - Zhang, Feifei (CNS Neurosci Ther, 2020)
AIM: Over 90% of patients receiving orthodontic treatment experience clinically significant pain. However, little is known about the neural correlates of orthodontic pain and which has therefore been investigated in the present study of healthy subjects using an experimental paradigm. METHODS: Resting‐state functional magnetic resonance imaging (rsfMRI) was performed in 44 healthy subjects 24 hours after an elastic separator had been introduced between the first and the second molar on the right side of the lower jaw and in 49 age‐ and sex‐matched healthy control (HC) subjects. A K‐means clustering algorithm was used to identify functional gray matter (GM) and white matter (WM) resting‐state networks, and differences in functional connectivity (FC) of GM and WM between the group of subjects with experimental orthodontic pain and HC were analyzed. RESULTS: Twelve GM networks and 14 WM networks with high stability were identified. Compared with HC, subjects with orthodontic pain showed significantly increased FC between WM12, which includes posterior thalamic radiation and posterior cingulum bundle, and most GM networks. Besides, the WM12 network showed significant differences in FC with three GM‐WM loops involving the default mode network, dorsal attention network, and salience network, respectively. CONCLUSIONS: Orthodontic pain is shown to produce an alteration of FC in networks relevant to pain processing, which may be mediated by a WM network relevant to emotion perception and cognitive processing.